GENETIC DIVERSITY AMONG SWEET POTATO CROPS CULTIVATED BY TRADITIONAL FARMERS - Vargas, Pablo Forlan [UNESP] (2018)
The genetic variability within the crop species Ipomoea batatas is broad, hence, in order to support future breeding programs it is of the utmost importance that germplasm banks be created, conserved, and characterized. Therefore, the objective of this work was to rescue and evaluate the genetic divergence in sweet potato accessions collected in traditional communities of Vale do Ribeira Paulista. Sweet potato samples were collected from quilombos, indigenous villages, caicaras communities, and small farms. The study was conducted between February 2013 and August 2014 in a randomized block design with three replications. Genetic material included 95 collected accessions and two commercial cultivars. Morphological characteristics of the accessions were evaluated and distances in the genetic distance matrix were estimated by means of multi-category variables, the data being subsequently clustered by the Tocher method. Analysis of the relative contribution of each characteristic and phenotypic correlation of descriptors was also performed. Results evidenced wide genetic diversity among the sweet potato accessions collected in Vale do Ribeira, which were not grouped according to the collection point. The descriptors that contributed more than 60% of genetic diversity included: leaf size, general leaf profile, immature leaf color, petiole pigmentation, predominant branch color, branch secondary color, stem length, cortical thickness, predominant periderm color, and periderm color intensity. Correlations between morphological descriptors was observed in 22.26% of the paired traits.